2015
DOI: 10.3892/ol.2015.2882
|View full text |Cite
|
Sign up to set email alerts
|

Reactive nodular fibrous pseudotumor involving the gastrointestinal tract and mesentery: A case report and review of the literature

Abstract: Reactive nodular fibrous pseudotumor (RNFP) is a tumor-like lesion that is characterized by reactive fibroblast/myofibroblast proliferation within collagenic hyalinized stroma, due to its association with injury or inflammation. The current study describes the case of a 60-year-old female with a history of abdominal surgery and abdominal pain. Upon laparoscopy, multiple nodules attached to the outer layer of the colon and mesentery were identified, and therefore, complete surgical excision was performed. Macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These lesions were first described by Yantiss et al 2 in 2003 and to date have only been reported as case reports or small case series. 3,4 These nodules often arise in the mesentery and have also been described arising within the gastric wall. 5 They may present with multiple nodules mimicking metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions were first described by Yantiss et al 2 in 2003 and to date have only been reported as case reports or small case series. 3,4 These nodules often arise in the mesentery and have also been described arising within the gastric wall. 5 They may present with multiple nodules mimicking metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%